The Role of Bissu and Their Existence in Modern Bugis Society of South Sulawesi - Rahmat, Laodemuh; Hartono; Purnomo, Sucipto Hadi (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
In the period before the influence of Islam entered the Bugis Bone kingdom, the Bugis Kingdom was always known for its mabissu tradition. The word bissu itself comes from the word "bessi" or mabesi which means a clean and holy creature. In the ancient Bugis tradition, apart from female bissu, there were also women. male bissu or waria. In Bugis culture in the past, bissu had a high position and were highly respected as well as being mouthpieces for the king and his people, as well as everything that related to the ritual ceremonies of the Bugis kingdom would not take place without bissu. The bissu are also believed to be intermediaries conveying revelations from God to be conveyed to the world. This is possible because the bissu have the ability to master the torilangi language (the language of the sky) where this language can only be known by them and the gods, with this privilege the existence of the bissu is still maintained. among the Bugis tribe to this day. However, in the current era of modernization, many bissu have changed professions to become indoboting (bridal make-up artists) and wedding dressers in order to fulfill their daily needs, because of this profession, many bissu experience social discrimination carried out by people who have minimal knowledge about bissu.